1963
DOI: 10.1017/s0079497x00015449
|View full text |Cite
|
Sign up to set email alerts
|

The Lower and Middle Palaeolithic Industries of the English East Midlands

Abstract: The first palaeoliths to be described from this country were found in the south of England, particularly from the Thames Valley and East Anglia. In 1880 Boyd Dawkins wrote that tools of Drift Man were ‘conspicuous by their absence from the gravels north-west of a line passing through the Midland counties from Bristol to the Wash’. In 1897 John Evans (Evans 1897, 580), in the light of the Saltley find from the Birmingham district, questioned the view then current that their absence was due to glacial conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The occurrence of Lower Palaeolithic artefacts in the gravels of the Middle Trent (Posnansky, ) provided an important rationale for the funding of the TVPP. A key finding of the project was that the archaeology occurs predominantly in the gravel of the Etwall (= Upper Hilton) Terrace, which incorporates outwash from the Wragby glaciation, the Palaeolithic archive taking the form of a mixed, highly abraded and frost‐damaged assemblage that was swept from the pre‐MIS 8 landscape and incorporated in these sediments (Bridgland et al ., ).…”
Section: Evidence From the Tvpp 2: The ‘Hilton Terrace’ Glaciation Ofmentioning
confidence: 76%
“…The occurrence of Lower Palaeolithic artefacts in the gravels of the Middle Trent (Posnansky, ) provided an important rationale for the funding of the TVPP. A key finding of the project was that the archaeology occurs predominantly in the gravel of the Etwall (= Upper Hilton) Terrace, which incorporates outwash from the Wragby glaciation, the Palaeolithic archive taking the form of a mixed, highly abraded and frost‐damaged assemblage that was swept from the pre‐MIS 8 landscape and incorporated in these sediments (Bridgland et al ., ).…”
Section: Evidence From the Tvpp 2: The ‘Hilton Terrace’ Glaciation Ofmentioning
confidence: 76%
“…Handaxes of similar andesitic ash found in Leicestershire, Derbyshire, and Lincolnshire (Posnansky 1963;Graf 2002) are from an area too far east to have been glaciated by western ice and therefore could not have been introduced into that area from the north-west. If a natural source for the andesite in pre-existing glacial deposits can be ruled out, the only possible means of introducing it into the Midlands is by human transport.…”
Section: Synthesismentioning
confidence: 99%
“…Archaeological studies of quartzite in the 1980s (Moloney 1988;Moloney et al 1988) have revealed that, while these pebbles can be used quite easily as tools (once modified), manufacture from this raw material is not as easy to control as the working of flint. The nature of the quartzite in the region, generally found in pebble or cobble form, and often with internal flaws, means a knapper benefits from a 'less is more' approach (Moloney 1988 (Posnansky 1963), Worcestershire (Whitehead 1988), Warwickshire (Fennell & Shotton 1977), Leicestershire (Graf 2002), Lincolnshire (Graf 2002;J. Wymer, pers.…”
Section: Materials Of the Palaeolithic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several literature on archaeological research in Uganda such as Bishop and Posnansky (1960);; Shinnie (1960); Lanning (1953Lanning ( -1970; Marshall (1954); Morris (1956); Pearce and Posnansky (1963); Posnansky (1963); Posnansky and Cole (1963); Soper (1971);Sutton (1985Sutton ( -1998; Robertshaw (1994Robertshaw ( -2010 and, Reid (1994Reid ( -2016, indicate that research has been going on since the early 1920s. The foundation of this research was set by the staff of the Uganda Geological Survey Department, led by E.J.…”
Section: Background Of the Studymentioning
confidence: 99%